Normal colonic mucosa in hereditary non-polyposis colorectal cancer shows no generalised increase in somatic mutation. - Williams, G. T. (Nature Publishing Group, 1995)
Hereditary non-polyposis colorectal cancer (HNPCC) has recently been linked to germline defects of DNA repair genes. Colorectal tumours in HNPCC frequently show DNA microsatellite instability, but it is not certain whether this mutator phenotype occurs throughout the morphologically normal colonic mucosa. We have previously used the mPAS histochemical technique in human colorectal mucosa to identify a polymorphism for O-acetyltransferase activity that shows monogenic inheritance and to show that crypt-restricted loss of O-acetyltransferase activity in heterozygotes is due to somatic mutation. We have now used this histochemical technique to measure the somatic mutation frequency in the uninvolved colon of 12 heterozygous patients with HNPCC, 15 with ileocaecal Crohn's disease and 16 with sporadic colorectal cancer (CRC). HNPCC patients showed a significant increase in mutation frequency with age (Mann-Whitney U, P = 0.02). In HNPCC patients aged < 49 years the mean stem cell mutation frequency was significantly lower than in the slightly younger group of patients with Crohn's disease (0.8 +/- 0.9 x 10(-4) vs 3.5 +/- 3.3 x 10(-4), P < 0.01), probably reflecting an increased mutation rate relating to chronic mucosal damage in Crohn's disease. Although not statistically significant, the stem cell mutation frequency was slightly less in HNPCC patients > 50 years than in sporadic CRC cases (4.9 +/- 3.4 x 10(-4) vs 5.9 +/- 3.6 x 10(-4), P > 0.5). We conclude that germline defects in HNPCC do not result in a generalised increase in liability to mutation in normal colonic mucosa but that a second, somatic, event is required. We postulate that this second event occurs in crypt stem cells at low frequency, giving rise to scattered individual crypts composed of mutation-prone cells. The cells in these crypts are then at high risk of acquiring the mutations that lead to adenomas, and to rapid progression to carcinoma.